The Influence of Promotion, Price Perception, Convenience and Trust on Food and Beverage Purchasing Decisions Using Gofood Features (Gojek Application Study in West Jakarta) - Hareka, Muhammad Bimo; Harwani, Yuli (Dinasti International Journal of Digital Business Management, 2025)
The development of technology is currently experiencing very tight competition, especially in the world of transportation and one of them is in Indonesia which experiences quite significant transportation developments every year. This study aims to determine "The Effect of Promotion, Price Perception, Convenience and Trust on Food and Beverage Purchasing Decisions for Go Food Features (Gojek Application Study in West Jakarta)". The population in this study were Go-Food users in the West Jakarta area. The sample used in this study was 170 respondents with 17-30 and was calculated using the Rambut formula. The data collection method used a survey method, with a gform questionnaire research instrument. The sampling technique used purposive sampling and the approach used was the Structural Equation Model (SEM) with the SmartPLS analysis tool which stated that the Promotion variable had a positive and significant effect on Purchasing Decisions, the Price Perception variable had a positive and significant effect on Purchasing Decisions, the Convenience variable had a positive and significant effect on Purchasing Decisions, and the Trust variable had a positive and significant effect on Purchasing Decisions.